ISOLASI DAN KARAKTERISASI Ralstonia solanacearum PENYEBAB PENYAKIT LAYU BAKTERI PADA BIBITEucalyptus pellita KLON 077 AA DAN PENGHAMBATANNYA OLEH Pseudomonad fluorescens - Ahmad Fajarusshidiq; Irfandri Irfandri; Yunel Venita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
1Mahasiswa Fakultas Pertanian Universitas Riau2Dosen Fakultas Pertanian Universitas Riau  The research aims to isolate and characterize Ralstonia solanacearum cause bacterial wilt on seedlings of Eucalyptus pellitaclon 077 AA and its inhibition by Pseudomonad  fluorescens. The research was conducted at Laboratory of Plant Protection Department PT. Arara Abadi Group Sinarmas, Subregency of Tualang, Regency of Siak, Province of Riau from July to September 2019. The research was conducted using exploration and observation method and then analyzed descriptively. The observation parameters were morphological characteristic, physiological characteristic, virulency, inhibition ability by Pseudomonad fluorescens and bacterial race. Isolation of phatogenic bacteria from seedlings of Eucalyptus pellita clon 077 AA obtains two isolate which has similar morphological characteristic one each other. Physiological characteristic shows that R. solanacearum isolate Rs-2 has similar characters toR. solanacearum on colony colour in medium NAPSA+TZC, negative reaction on gram test, negative reaction on gram staining test, positive reaction on oxidase test and positive reaction on OF test. Virulency test of R. solanacearum isolate Rs-2 towards E. pellita seedlings shows positive reaction so R. solanacearum isolate Rs-2 is pathogenic. The inhibition zone that produced by Pseudomonad fluorescens towards R. solanacearum isolate Rs-2 is 17,3 mm in medium King’s B and 12,4 mm in medium NAPSA and classifies as strong and the mechanism of its inhibition is bacteriostatic. The pathology race test shows that R. solanacearum isolate Rs-2 is Ralstonia solanacearumon race 1.Keywords: Characterization, Eucalyptus pellita, isolation, Pseudomonad fluorescens, Ralstonia solanacearum